Factors that Influence Sustainable Interest Through Customer Satisfaction When Using the Bank Raya Application. - Dewi Retno Yuningsih; Agus Salim (Dinasti International Journal of Management Science, 2023)
This research aims to analyze the influence of product quality, promotion and service quality on sustainable interest mediated by customer satisfaction when using the Bank Raya Application. The population subjects of this research were PT. Bank Raya Indonesia, Tbk, while the subjects used as samples were 137 respondents. This research design uses quantitative methods. The data collection technique uses a questionnaire. This research was conducted using the SEM-PLS analysis method. The research results show that Product Quality has a significant positive effect on Continuing Interest in using the Bank Raya Application, promotions do not have a significant influence on Continuing Interest in using the Bank Raya Application. Service Quality has a significant positive effect on Continuing Interest in using the Bank Raya Application, there is no sign ificant influence between Promotion and Customer Satisfaction on using the Bank Raya Application. Service Quality has a significant effect on Customer Satisfaction when using the Bank Raya Application. Customer satisfaction has a significant effect on continued interest in using the Bank Raya application. Product Quality Influences Sustainable Interest through the mediation of Customer Satisfaction when using the Bank Raya Application. Promotion does not mediate the relationship between Customer Satisfaction and Continued Interest in using the Bank Raya Application. Service Quality significantly influences Sustainable Interest through the mediation of Customer Satisfaction with the use of the Bank Raya Application.